Biological Studies and Target Engagement of the 2-C-Methyl-D-Erythritol 4-Phosphate Cytidylyltransferase (IspD)-Targeting Antimalarial Agent (1R,3S)-MMV008138 and Analogs - Ghavami, Maryam (ACS Infect Dis, 2017)
Malaria continues to be one of the deadliest diseases worldwide, and the emergence of drug resistance parasites is a constant threat. Plasmodium parasites utilize the methylerythritol phosphate (MEP) pathway to synthesize isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP), which are essential for parasite growth. Previously, we and others identified that the Malaria Box compound MMV008138 targets the apicoplast and that parasite growth inhibition by this compound can be reversed by supplementation of IPP. Further work has revealed that MMV008138 targets the enzyme 2-C-methyl-D-erythritol 4-phosphate cytidylyltransferase (IspD) in the MEP pathway, which converts MEP and cytidine triphosphate (CTP) to cytidinediphosphate methylerythritol (CDP-ME) and pyrophosphate. In this work, we sought to gain insight into the structure–activity relationships by probing the ability of MMV008138 analogs to inhibit Pf IspD recombinant enzyme. Here, we report Pf IspD inhibition data for fosmidomycin (FOS) and 19 previously disclosed analogs and report parasite growth and Pf IspD inhibition data for 27 new analogs of MMV008138. In addition, we show that MMV008138 does not target the recently characterized human IspD, reinforcing MMV008138 as a prototype of a new class of species-selective IspD-targeting antimalarial agents.